Cu-mediated or metal-free alkylation of gem-dibromoalkenes with tertiary, secondary and primary alkyl Grignard reagents. (12th February 2021) - Deng, Yupian; Zhang, Xuxue; Liu, Chuan; Cao, Song
Abstract: A novel copper-mediated or transition-metal-free alkylation of gem -dibromoalkenes with tertiary, secondary and primary alkyl Grignard reagents was described. The outcomes of these reactions were found to be highly dependent on the reaction conditions and the type of Grignard reagents used. Specifically, the tertiary alkylation of gem -dibromoalkenes proceeded efficiently in the presence of 50 mol% CuCN or under transition-metal-free conditions, furnishing the tertiary alkyl-substituted monobromoalkenes or alkenes in high yields. Graphical abstract: Image 1 Highlights: gem -Dibromoalkenes are versatile building blocks for organic synthesis. The examples of tertiary alkylation of gem -dibromoalkenes are rare. Copper-mediated or transition-metal-free alkylation of gem -dibromoalkenes. Synthesis of tertiary alkyl-substituted monobromoalkenes or alkenes.